2012
DOI: 10.1038/modpathol.2012.119
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of HGAL/GCET2 in immunohistological algorithms: a comparative study in 424 cases of nodal diffuse large B-cell lymphoma

Abstract: Diffuse large B-cell lymphoma can be subclassified into at least two molecular subgroups by gene expression profiling: germinal center B-cell like and activated B-cell like diffuse large B-cell lymphoma. Several immunohistological algorithms have been proposed as surrogates to gene expression profiling at the level of protein expression, but their reliability has been an issue of controversy. Furthermore, the proportion of misclassified cases of germinal center B-cell subgroup by immunohistochemistry, in all r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
6
0
2
Order By: Relevance
“…Human germinal center‐associated lymphoma (HGAL) is a B‐cell specific marker the expression of which is observed in the cytoplasm of normal germinal center B cells and lymphomas of GCB derivation . Gualco et al reported that the inclusion of HGAL in the Hans immunohistological algorithm improved the detection of the GCB subtype of DLBCL . In our study, the HGAL staining results matched those predicted by the Hans model in 82% (9/11) of cases.…”
Section: Discussionsupporting
confidence: 71%
“…Human germinal center‐associated lymphoma (HGAL) is a B‐cell specific marker the expression of which is observed in the cytoplasm of normal germinal center B cells and lymphomas of GCB derivation . Gualco et al reported that the inclusion of HGAL in the Hans immunohistological algorithm improved the detection of the GCB subtype of DLBCL . In our study, the HGAL staining results matched those predicted by the Hans model in 82% (9/11) of cases.…”
Section: Discussionsupporting
confidence: 71%
“…GCET1 positivity in DLBCL ranges from 15% to 47% in the literature [ 18 , 32 , 33 , 34 , 35 , 36 ]. In the present study, GCET1 was found to be positive in 35.4% of cases, in accordance with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Meyer et al [15] included GCET1 and LMO2 as GC markers and FOXP1 as ABC marker. HGAL/GCET2 is also considered to be a GC marker [16]. CD30 positivity may be observed in 10-20% patients with DLBCL [17].…”
Section: Discussionmentioning
confidence: 99%